STRATEGI PENGEMBANGAN KAMPUNG ADAT KUTA SEBAGAI DESTINASI WISATA - Anggi Setiadi; Agus Yadi Ismail; Deni Deni (Faculty of Forestry and Environment, Universitas Kuningan, 2023)
Kuta Traditional Village development is faced with a lack of human resources who understand the importance of tourism awareness, lack of support to improve infrastructure and development budgets are still a major problem for rural communities to develop tourist objects and make their villages progress to become tourist villages. The objectives of this study are 1) Knowing the management strategy for the development of Kuta Traditional Village as a tourist destination; 2) Knowing the development strategy of the Kuta Traditional Village. The research method used was a questionnaire and FGD which were then analyzed using IFAS and EFAS as well as a SWOT analysis. From the research results it is known that 1) the authenticity of the Kuta traditional village; 2) Traditional social life; 3) Customs and customs that are still adhered to; 4) Traditional ceremonies are still being held; and 5) The sacredness of the Leuweung Gede forest is a potential that can make Kuta Traditional Village a tourist destination. The IFAS and EFAS analysis shows a score of 2.07 for strengths, 1.78 for weaknesses and 1.40 for opportunities and 1.53 for threats. In the SWOT diagram, the position of the Kuta Traditional Village is in quadrant II. Diversification (0.14 x-axis and -0.06 y-axis), which means that Kuta Traditional Village is in a position that has threats but still has strength, to minimize these threats the strategy that can be used is the ST strategy.Pengembangan Kampung Adat Kuta dihadapkan dengan kurangnya sumberdaya manusia yang mengerti akan pentingnya kesadaran pariwisata, kurangnya dukungan untuk mneingkatkan infrastuktur merupakan dan anggaran pengembangan masih menjadi permasalahan utama bagi masayarakat desa untuk mengembangkan objek wisata dan menjadikan desanya maju untuk menjadi desa wisata. Tujuan dari penelitian ini adalah 1) Mengetahui strategi pengelolaan pengembangan Kampung Adat Kuta sebagai destinasi wisata; 2) Mengetahui strategi pengembangan Kampung Adat Kuta. Metode penelitian yang digunakan adalah kuesiner dan FGD yang kemudian dianalisis menggunakan IFAS dan EFAS serta analisis SWOT. Dari hasil penelitian diketahui bahwa 1) Keaslian kampung adat kuta; 2) Kehidupan sosial masyarakat yang masih tradisional; 3) Adat dan istiadat yang masih dipegang teguh; 4) Masih sering dilaksanakannya upacara adat; dan 5) Kesakralan hutan leuweung gede merupakan potensi yang dapat menjadikan Kampung Adat Kuta sebagai destinasi wisata. Analisis IFAS dan EFAS menunjukan skor 2.07 untuk kekuatan, 1.78 untuk kelemahan dan 1.40 untuk peluang dan 1.53 untuk ancaman. Dalam diagram SWOT posisi Kampung Adat Kuta berada pada kuadran II. Diversifikasi (sumbu x 0.14 dan sumbu y -0.06) yang artinya Kampung Adat Kuta berada dalam posisi yang memiliki ancaman namun masih memiliki kekuatan, untuk meminimalkan ancaman tersebut strategi yang dapat digunakan adalah strategi ST